ANALISIS HIDROLIKA ALIRAN SALURAN SEKUNDER DI DESA PARIT BARU KECAMATAN SELAKAU KABUPATEN SAMBAS DENGAN MENGGUNAKAN SOFTWARE HEC-RAS - Akbar Syawaludin, Mardhika; ANGGRAINI, IKA MUTHYA; Wahyu, Zainal (Jurnal Teknologi Infrastruktur, 2022)
Floods can occur due to high rainfall, intensity, or damage due to wrong land use. In addition, floods can also be caused by climate change, disruption of the flow of rainwater in rivers, reduction of the surface area that absorbs water due to the construction of many buildings and the occurrence of forest destruction, overflow of the main rivers that pass through residential and urban areas, due to the intensity of rainfall. which is high in the upper reaches of the river which also often causes flooding. Knowing the planned flood discharge with return periods of 2, 5 and 10 years and simulating the flood water level on the channel cross-section that is experiencing overflow using HEC-RAS software with return periods. The data needed in the analysis include hydrological analysis, hydraulic analysis, river geometry data input, and discharge data input. Based on the results of hydrological analysis using the Nakayasu Synthetic Unit Hydrograph method in the secondary canal of Parit Village, Selakau District, Sambas Regency with a return period of Q2th = 56.13 m3/second, Q5th = 56.18 m3/second, and Q10th = 56.21 m3/second. Based on the results of the analysis using the HEC-RAS 5.0.7 program with calculated debits from the hydrological results, the potential for flooding is generated at all stations from upstream to downstream.